(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The twin concepts of "global" and "local" have close associations with the phenomenon of globalisation. In general terms, globalisation refers to those greater interconnections between countries resulting in broad economic changes and consumption patterns, advances in communication technology and new media that have transformed human life especially in the field of language education (Block and Cameron 2002) and the propagation of cultural values and practices. It has also resulted in the transformation and reconstruction of identities on a number of levels (Mesthrie and Swann 2010, 105). In the popular imagination, globalisation is seen as a phenomenon that is synonymous with homogenisation or Westernisation. This is arguable as globalisation has also triggered a spirit of resistance towards the English language and Western cultural forms and practices as part of their appropriation and domestication to local needs and purposes (Clyne and Sharifian 2008; Sharifian 2009; 2013). In fact, globalisation is perceived as an agent of "glocalisation" (Robertson 1995) as it encourages a dynamic and constructive interplay of the global and the local. In this connection, globalisation is instrumental in the rapid usage of English by speakers in the world today. It has spurred the localisation of English as evidenced in the many varieties of English that have emerged over time, a phenomenon referred to as the "glocalisation of English" (Sharifian 2013, 2).